IMPLEMENTASI SISTEM PEMBAYARAN DIGITAL DiGiPay SATU DALAM PENGELOLAAN BELANJA NEGARA DI MTsN 12 TABALONG - Latifah Latifah (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
Digital transformation in public sector financial management has become an important agenda of the Indonesian government, including in public educational institutions. One form of its implementation is the adoption of the DiGiPay Satu digital payment system developed by the Directorate General of Treasury to enhance transparency, efficiency, and accountability in state expenditure. This study aims to provide an in-depth analysis of the implementation of DiGiPay Satu in managing state expenditure at MTsN 12 Tabalong and to identify the challenges encountered in its application. The research employs a qualitative approach with an intrinsic case study design. Data were collected through in-depth interviews with key informants, limited participatory observation, and documentation, and were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, guided by the frameworks of Digital Governance and Institutional Theory. The findings indicate that the implementation of DiGiPay Satu has not yet been optimal due to cyclical system performance degradation at the beginning of each month, the complexity of transaction workflows, low digital literacy and resistance among human resources, and the limited number of vendors integrated into the system. Nevertheless, the implementation of DiGiPay Satu has had a positive impact on improving transparency and accountability in madrasah financial management through digitally recorded and integrated transactions. This study concludes that the success of digitalizing state expenditure management in educational institutions is determined not only by technological readiness but also by human resource preparedness, changes in work culture, and the strengthening of supporting ecosystems, particularly the involvement of local vendors. ABSTRAK Transformasi digital dalam pengelolaan keuangan sektor publik menjadi agenda penting pemerintah Indonesia, termasuk pada satuan pendidikan negeri. Salah satu bentuk implementasinya adalah penerapan sistem pembayaran digital DiGiPay Satu yang dikembangkan oleh Direktorat Jenderal Perbendaharaan untuk meningkatkan transparansi, efisiensi, dan akuntabilitas belanja negara. Penelitian ini bertujuan untuk menganalisis secara mendalam implementasi DiGiPay Satu dalam pengelolaan belanja negara di MTsN 12 Tabalong serta mengidentifikasi tantangan yang dihadapi dalam penerapannya. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus intrinsik. Data dikumpulkan melalui wawancara mendalam dengan informan kunci, observasi partisipatif terbatas, dan dokumentasi, kemudian dianalisis menggunakan model analisis interaktif Miles, Huberman, dan Saldaña dengan kerangka teori Digital Governance dan Institutional Theory. Hasil penelitian menunjukkan bahwa implementasi DiGiPay Satu belum berjalan optimal akibat adanya degradasi performa sistem yang bersifat siklus pada periode awal bulan, kompleksitas alur transaksi, rendahnya literasi digital serta resistansi sumber daya manusia, dan keterbatasan jumlah vendor yang terintegrasi dengan sistem. Meskipun demikian, penerapan DiGiPay Satu memberikan dampak positif terhadap peningkatan transparansi dan akuntabilitas pengelolaan keuangan madrasah melalui pencatatan transaksi secara digital dan terintegrasi. Penelitian ini menyimpulkan bahwa keberhasilan digitalisasi pengelolaan belanja negara di satuan pendidikan tidak hanya ditentukan oleh kesiapan teknologi, tetapi juga oleh kesiapan sumber daya manusia, perubahan budaya kerja, serta penguatan ekosistem pendukung, khususnya keterlibatan vendor lokal.